Varus malalignment of cementless hip stems provides sufficient primary stability but highly increases distal strain distribution. (October 2018) - Fottner, Andreas; Woiczinski, Matthias; Kistler, Manuel; Schröder, Christian; Schmidutz, Tobias F.; Jansson, Volkmar; Schmidutz, Florian
Abstract: Background: Varus position of cementless stems is a common malalignment in total hip arthroplasty. Clinical studies have reported a low rate of aseptic loosening but an increased risk for thigh pain. This in vitro study aimed to evaluate these clinical observations from a biomechanical perspective. Methods: A conventional cementless stem (CLS Spotorno) was implanted in a regular, straight (size 13.75) as well as in a varus position (size 11.25) in 6 composite femora (Sawbones), respectively. Primary stability was assessed by recording 3-dimensional micromotions under dynamic load bearing conditions and stress shielding was evaluated by registering the surface strain before and after stem insertion. Findings: Primary stability for stems in varus malposition revealed significantly lower micromotions ( p < 0.05) for most regions compared to stems in neutral position. The greatest difference was observed at the tip of the stem where the straight aligned implants exceeded the critical upper limit for osseous integration of 150 μm. The surface strains for the varus aligned stems revealed a higher load transmission to the femur, resulting in a clearly altered strain distribution. Interpretation: This biomechanical study confirms the clinical findings of a good primary stability of cementless stems in a varus malposition, but impressively demonstrates the altered load transmission with the risk for postoperative thigh pain. Highlights: Biomechanical differences of hip stems in normal straight and varus position. Comparison of 3-dimensional micromotions and surface strain distributions Varus position resulted in lower micromotions. Varus aligned stems clearly altered strain distribution.